2014
DOI: 10.3329/bjas.v43i1.19383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of Dhania seed (Coriandrum sativum) on the performance of broiler

Abstract: A total of 72 as hatched Cobb 500 broilers were fed ad libitum on a diet with 0 %, 0.5 %, 1.0 % and 1.5 % of coriander seed meal (CSM) to assess its feeding value. Treatment group with 1.5 % of CSM significantly (p<0.05) affected live weight of broilers at the age of 28 and 35 days. Among the dietary groups there is no significant difference in feed intake and feed efficiency. Meat yield characteristics especially abdominal fat level decreased significantly (p<0.01) at 1.5 % level of CSM. Cost of product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
6
4
0
Order By: Relevance
“…Abo Omar et al (2016) revealed that the presence of antioxidants and phenolic substance in herbal extract enhanced the carcass breast of broiler chicken by 1.2%. Furthermore, the dressing percentage with skin in this trial was in agreement with other studies ( Rashid et al , 2014 ; Naeemasa et al , 2015 ) which reported that the use of herbal plants had no effect on the dressing percentage of broiler chickens. However, the heart weights were significantly increased ( p < 0.05) in treatment diets, where the highest weight was observed at 2.5% when compared with the control group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Abo Omar et al (2016) revealed that the presence of antioxidants and phenolic substance in herbal extract enhanced the carcass breast of broiler chicken by 1.2%. Furthermore, the dressing percentage with skin in this trial was in agreement with other studies ( Rashid et al , 2014 ; Naeemasa et al , 2015 ) which reported that the use of herbal plants had no effect on the dressing percentage of broiler chickens. However, the heart weights were significantly increased ( p < 0.05) in treatment diets, where the highest weight was observed at 2.5% when compared with the control group.…”
Section: Discussionsupporting
confidence: 92%
“…The FI was not affected by the three levels of coriander and these results were in agreement with other studies (Saeid and Al-nasr, 2010;Al-Jaff, 2011;Amad et al, 2011;Abadi and Andi, 2014;Abou-Elkhair et al, 2014;Rashid et al, 2014). This finding may be attributed to the chemical composition of the basal diets, which can be due to the fluctuation of the environmental temperature that reflected inside the room and relative humidity during the last couple of experiment weeks, which was confirmed by the thermostatic theory described by Ferket and Gernat (2006), who reported that the major environmental factor in controlling FI is ambient temperature, which leads to increased water consumption and in turn it decreases the FI.…”
Section: Feed Intakesupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, our results are in agreement with those reported by ; Al‐Jaff (); Saeid and AL‐Nasry () and Naeemasa et al () who reported that supplementing broiler diets with 0.3%, 0.2% coriander seed and 952 mg/kg of coriander extract, respectively, improved the overall growth performance. Coriander seed meal in broiler diets was found to have antioxidant properties that may act as natural growth promoters, and also resulted in improvements in broiler weight gain (Rashid et al, ). Our results also are supported by those of Rajeshwarim and Andallu (), who reported that the essential oils of coriander are excellent appetite stimulators and stimulate the appropriate secretion of enzymes and some digestive juices in the stomach.…”
Section: Resultsmentioning
confidence: 99%